JEPT 2020
DOI: 10.21926/jept.2004017
|View full text |Cite
|
Sign up to set email alerts
|

Further Understanding of Uncertainties in the Impedance Spectrum of the Polymer Electrolyte Fuel Cell due to Inductive Effects and Oxygen Diffusion Time Constant

Abstract: In this study, uncertainties during the assessment of the electrochemical impedance spectrum of the polymer electrolyte fuel cell (PEFC) attributed to inductive artefacts at high frequencies and inductive loops at low frequencies as well as oxygen diffusion time constant are discussed. A validated impedance model represented as an equivalent electrical circuit of a PEFC allowed the simulation of the effect of inductive artefacts, inductive loops and oxygen diffusion time constant on electrochemical impedance s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…1. In a previous study [60], it was demonstrated that inductive loops shrink the impedance spectrum where the negative imaginary component -Z'' intercepts the real component Z' at low frequencies. EIS measurements in PEFCs [45,61].…”
Section: Results With Eq 1 (No Inductive Loop)mentioning
confidence: 96%
“…1. In a previous study [60], it was demonstrated that inductive loops shrink the impedance spectrum where the negative imaginary component -Z'' intercepts the real component Z' at low frequencies. EIS measurements in PEFCs [45,61].…”
Section: Results With Eq 1 (No Inductive Loop)mentioning
confidence: 96%
“…But when stronger inductor component exists, it has to be considered in ECM modeling. [15] Klotz and Shin reported that in the high-frequency range (>1 kHz) certain inaccuracies may occur due to the wiring inductivities. [13,16] Similar effects coming from the instrument setup (potentiostat/power supply internal components, i.e., cables, voltage, and current amplifiers) were also discussed by Erinmwingbovo et al, in a study on instrument artifacts on EIS.…”
mentioning
confidence: 99%